Civil conflict, cash transfers, and child nutrition in Yemen - Ecker, Olivier; Maystadt, Jean-Francois (Households in Conflict Network, 2021)
The most dramatic outcomes of protracted civil conflict include increased malnutrition among children and the resulting consequences for lifelong health and prosperity. Little is known about how to mitigate the nutritional impact of conflict. Knowing the potential of economic interventions is particularly important for post-conflict reconstruction, when the threat of violence resurgence is high. We use quarterly panel data from Yemen to estimate the impact of civil conflict on child nutrition in Yemen and the effects of unconditional cash transfers in mitigating the adverse nutritional impact. Our results show that a one-standard-deviation increase in armed conflict intensity reduces the weight-for-height z-scores (WHZ) of children by 9.6%, on average. We also find that the studied cash transfer program reduces the nutritional impact by 35.8% for WHZ. Our analysis suggests that if relative stability is restored, unconditional cash transfer programs can be an effective tool to curb rising acute child malnutrition in situations of complex emergencies.